2010
DOI: 10.1111/j.1460-9592.2010.03362.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized trial comparing supraglottic airways for flexible bronchoscopy in children

Abstract: In this trial, PVC single-use laryngeal masks were inferior to the silicone cLMA and Boss Systems laryngeal masks for flexible bronchoscopy in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…We included published prospective human clinical trials where the AuraOnce was compared with the LMA Classic, LMA Unique and Soft Seal. A total of nine articles included one of these comparisons; however, one article was excluded as the study was conducted in children . A flow diagram of study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We included published prospective human clinical trials where the AuraOnce was compared with the LMA Classic, LMA Unique and Soft Seal. A total of nine articles included one of these comparisons; however, one article was excluded as the study was conducted in children . A flow diagram of study selection is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When a fibrescope is used to visualize and intubate the larynx via a SAD, an important factor in success is the ease of manipulation of the fibreoptic device. The silicone classic laryngeal mask airway offers less resistance to bronchoscopic manipulation when compared to single‐use polyvinyl chloride (PVC) SADs . Such seemingly, small individual components of the difficult intubation package mark the difference between success and failure at the extremes of difficulty when dealing with challenging pediatric airways.…”
Section: Supraglottic Airway Devicesmentioning
confidence: 99%
“…It is expensive, can be awkward to set up, and is difficult to clean, and so is less likely to be used routinely to maintain skills. In children, however, it has the advantage of facilitating intubation through the laryngeal mask airway, which is handy as a large proportion of challenging airways can be successfully managed with a laryngeal mask airway (although the bronchoscope may be gripped by the shaft of some brands of single‐use laryngeal mask airways (22)). The fiberoptic bronchoscope is also available in a size that is suitable even for a neonate.…”
Section: The Challenging Laryngoscopymentioning
confidence: 99%